THE EFFORTS TO IMPROVE SOCIAL SCIENCE LEARNING OUTCOMES USING COOPERATIVE LEARNING PICTURE AND PICTURE LEARNING AT PRIMARY SCHOOL - Mintarwati Mintarwati (Universitas Tanjungpura, 2020)
The study was a classroom action research conducted to improve the learning process, improving student learning outcomes. In this study, learning was carried out using a picture and picture cooperative learning model to aim for students to be active, cooperative, and motivated towards the learning carried out. The study was conducted in 2 cycles, each cycle consisting of planning the implementation of the action, observation, and reflection with 33 students consisting of 15 boys and 18 girls. The research main problem was the low learning outcomes of the sixth-grade students of SD Negeri 10 Sungai Kakap about knowing warrior figures. The purpose of this study was to determine student learning outcomes in IPS subjects. The results of the study using the cooperative learning method of picture and picture learning in the material to recognize warriors in class VI showed that the use of the cooperative learning model learning picture and picture in IPS subjects recognized warriors against Dutch colonialism in VI grade at SDN 10 Sungai Kakap at semester 2 of the 2018-2019 academic year can improve learning outcomes, namely 84.84% in cycle 1 to 90.90%. In cycle 2, with student learning outcomes, the highest score was 80, and the lowest was 50 in the pre-cycle being the highest score of 90, and the lowest was 65 in cycle 1 becomes the highest score of 100 and the lowest score of 65 in cycle 2.